Epidemiological assessment and outbreak report of Trypanosoma vivax in dairy cattle from the Brazilian Semiarid region - Lima Neto, Basílio Felizardo; Silva, Jordania Oliveira; Alvares, Felipe Boniedj Ventura; Batista, Samira Pereira; Silva Filho, Geraldo Moreira; Medeiros, Gláucia Diojânia Azevedo; Rodrigues, Carla Monadeli Filgueira; Fermino, Bruno Rafael; Vilela, Vinícius Longo Ribeiro; Feitosa, Thais Ferreira (Frontiers in Animal Science, 2025)
This study aimed to estimate the prevalence and identify risk factors associated with Trypanosoma vivax infection in dairy cattle herds in the Brazilian Semiarid region, as well as report an outbreak of trypanosomiasis. A total of 390 cattle blood samples were collected from 61 farms in the states of Ceará e Paraíba, and a conventional PCR was performed for the diagnosis of T. vivax. Positive samples were bidirectionally sequenced. An epidemiological questionnaire was applied on each farm, and the resulting data were subjected to univariate and multivariate analyses to identify potential risk factors. An outbreak was detected in the municipality of Orós, Ceará, where cases of abortion and estrus repetition were reported among cows. Of the 390 samples analyzed, 1.02% (4/390) tested positive for T. vivax. No statistically significant risk factors were identified. All positive samples originated from the farm in Orós, where 80% (4/5) of the tested animals were infected. Similarity analysis using BLAST revealed 100% identity with T. vivax isolates previously reported in donkeys, sheep, and cattle from the Brazilian semi-arid region, and high similarity with isolates from South American countries and West Africa. In the phylogenetic analysis, sequences TviBrCe13 and TviBrCe14 clustered with isolates from the Brazilian Semiarid region, as well as with South American and West African strains. It was concluded that the prevalence of T. vivax in the Brazilian Semiarid region is low, although the area remains susceptible to outbreak events.